Nodule size as predictive factor of efficacy of radiofrequency ablation in treating autonomously functioning thyroid nodules. (4th July 2018) - Cesareo, R.; Naciu, A. M.; Iozzino, M.; Pasqualini, V.; Simeoni, C.; Casini, A.; Campagna, G.; Manfrini, S.; Tabacco, G.; Palermo, A.
Abstract: Context: No defined pre-treatment factors are able to predict the response to radiofrequency ablation (RFA) of an autonomously functioning thyroid nodule (AFTN). Objective: Primary endpoint was to evaluate the success rate of RFA to restore euthyroidism in a cohort of adult patients with small solitary AFTN compared with medium-sized nodules. Secondary endpoints included nodule volume reduction and rate of conversion from hot nodules to cold using scintiscan. Methods: This was a 24-month prospective monocentric open parallel-group trial. Twenty-nine patients with AFTN were divided into two groups based on thyroid volume: 15 patients with small nodules (<12 mL) in group A and 14 patients with medium nodules (>12 mL) in group B. All patients underwent a single session of RFA and were clinically, biochemically, and morphologically evaluated at baseline and at 1, 6, 12 and 24 months after treatment. Results: After RFA, there was greater nodule volume reduction in group A compared with group B ( p < 0.001 for each follow-up point). In group A, there was a greater increase in TSH levels than in group B at 6 ( p = 0.01), 12 ( p = 0.005), and 24 months ( p < 0.001). At 24 months, the rate of responders was greater in group A than in group B (86 vs. 45%; p < 0.001). In group A, 86% of nodules converted from hot to cold compared with 18% in group B ( p < 0.001). Conclusions: A single session of RFA was effective in restoring euthyroidism in patients with small AFTNs. Nodule volume seems to be a significant predictive factor of the efficacy of RFA in treating AFTN.